Incidencia de colelitiasis en pacientes atendidos en el servicio de cirugía del hospital Julius Doepfner de Zamora mayo-agosto 2015 - Rivera Zambrano, Beatriz Elizabeth (2016)
The purpose of this research was to determine the incidence of gallstones in patients treated at the Hospital Surgery area Julius Doepfner. The methodology used was observational, prospective, transversal, descriptive, field, bibliographic. For the implementation and development of the research work an observation guide was used to obtain data of the population and the survey technique with his instrument the questionnaire administered to 48 patients diagnosed with cholelithiasis, obtaining as results that the highest percentage of patients formed the study are between the ages of 21 to 30 years with 22.20%, with married civil state (or) with 45.68%, a female 58.44% of mixed ethnicity and secondary level, public employee or private activity, in terms of urban residence. The incidence of cholelithiasis is 17.75%. The incidence in relation to age groups is presented in ages less than 40 years with the cumulative percentage of 12.76%, the female with 11.52%, mixed race ethnicity showed higher indices 1605, in relation to the symptoms that led to the patients to seek help typical right flank pain and epigastric pain was evident, the incidence was also associated with obesity and overweight. As a contribution to the problem encountered an educational plan aimed at preventing and sensitize patients to prevent further cases of cholelithiasis either in their family or community environment was developed. Concluding that cholelithiasis is high incidence of mixed ethnicity with 81.25%, in the age of 21-40 years with the 22.92% more frequent; and that incidents factors were toxic consumption, overweight and obesity. Keywords. Incidence, Cholelithiasis, Patients, Area Surgery